Jelleines: a family of antimicrobial peptides from the Royal Jelly of honeybees (Apis mellifera) - Fontana, R.; Mendes, M. A.; de Souza, B. M.; Konno, K.; Cesar, LMM; Malaspina, O.; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2004)
Four antimicrobial peptides were purified from Royal Jelly of honeybees, by using reverse phase-HPLC and sequenced by using Q-Tof-MS/MS: PFKLSLHL-NH2 (Jelleine-I), TPFKLSLHL-NH2 (Jelleine-II), EPFKLSLHL-NH2 (Jelleine-III), and TPFKLSLH-NH2 (Jelleine-IV). The peptides were synthesized on-solid phase, purified and submitted to different biological assays: antimicrobial activity, mast cell degranulating activity and hemolysis. The Jelleines-I-III presented exclusively antimicrobial activities against yeast, Gram+ and Gram- bacteria; meanwhile, Jelleine-IV was not active in none of the assays performed. These peptides do not present any similarity with the other antimicrobial peptides from the honeybees; they are produced constitutively by the workers and secreted into Royal Jelly. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: royal jelly; Africanized honeybees; Apis mellifera; mass spectrometry; antimicrobial peptides